Fire metaphors : the discourse of awe and authority - Charteris-Black, Jonathan, 1955- (Bloomsbury Academic, 2017)
"This detailed study of fire metaphors provides a deep understanding of the purposeful work of metaphor in discourse. It analyses how and why fire metaphors are used in discourses of awe (mythology and religion) and authority (political speeches and media reports). Fire serves as a productive and salient lexical field for metaphors that seek to create awe and impose authority. These metaphors offer a rich linguistic and conceptual resource for authors of mythologies, theologies, literature, speeches and journalism, and provide insight into the rich interplay of thought, language and culture. This book explores the purpose of fire metaphors in genres ranging from the Norse sagas to religious texts, from Shakespeare to British and American political speeches. Ultimately it arrives at an understanding of the rhetorical work that metaphor accomplishes in communicating evaluations and ideologies."--Bloomsbury Publishing